Prevalence of long face pattern in Brazilian individuals of different ethnic backgrounds (Journal of Applied Oral Science, 2013)
Objective: The long face pattern is a facial deformity with increased anterior total facial height due to vertical excess of the lower facial third. Individuals with long face may present different degrees of severity in vertical excess, as well as malocclusions that are difficult to manage. The categorization of vertical excess is useful to determine the treatment prognosis. This survey assessed the distribution of ethnically different individuals with vertical excess according to three levels of severity and determined the prevalence of long face pattern. Material and Methods: The survey was comprised of 5,020 individuals of Brazilian ethnicity (2,480 females and 2,540 males) enrolled in middle schools in Bauru-SP, Brazil. The criterion for inclusion of individuals with vertically impaired facial relationships was based on lip incompetence, evaluated under natural light, in standing natural head position with the lips at rest. Once identified, the individuals were classified into three subtypes according to the severity: mild, moderate, and severe. Then the pooled sample was distributed according to ethnical background as White (Caucasoid), Black (African descent), Brown (mixed descent), Yellow (Asian descent) and Brazilian Indian (Brazilian native descent). The Chi-square (χ 2 ) test was used (p